OPINI AUDIT, TINGKAT KEMANDIRIAN, DAN TIPE PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN INFORMASI - Annisa Murni; Sri Rahayu; Djusnimar Zultilisna (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
This research aims to analyze the effect of the audit opinion, level of independence, and the type of local government to the level of disclosure of information on the official website of the local Government of Central Java province in 2014-2015. Sampling techniques used in this study is a purposive and retrieved samples of as many as 25 local governments. Methods of data analysis used were descriptive and multiple regression. The results showed that the audit opinion, level of independence, and the type of local government effect simultaneously against the level of disclosure of information on the official website of the local government in the province of Central Java. Partially, the audit opinion and the types of local government that have an impact on the level of disclosure of information on the official website of the local government in the province of Central Java. Level of independence has not an impact, partially.